2015
DOI: 10.1007/s12035-015-9231-1
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of B cell CLL/Lymphoma 11B Gene Expression Represses Glioma Cell Growth

Abstract: B cell CLL/lymphoma 11B (Bcl11b), a C2H2 zinc finger transcription factor, not only serves as a critical regulator in development but also plays the controversial role in T cell acute lymphoblastic leukemia (T-ALL). We previously found that the enriched expression of Bcl11b was detected in high tumorigenic C6 glioma cells. However, the role of Bcl11b in glioma malignancy and its mechanisms remains to be uncovered. In this study, using the lentivirus-mediated knockdown (KD) approach, we found that Bcl11b KD in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…1. B cell lines: Naïve B cells can differentiate into antibody-secreting plasma cells after being stimulated by antigen (Liao et al, 2016). Our study found that naïve B cell was a significant decrease in gliomas, meanwhile, the plasma cells were significant increased.…”
Section: Discussionmentioning
confidence: 66%
“…1. B cell lines: Naïve B cells can differentiate into antibody-secreting plasma cells after being stimulated by antigen (Liao et al, 2016). Our study found that naïve B cell was a significant decrease in gliomas, meanwhile, the plasma cells were significant increased.…”
Section: Discussionmentioning
confidence: 66%
“…Based on our previous findings that Bcl11b-KD reduced the expression of stemness-related genes (Sox2 and Bmi1) in glioma cells ( Liao et al, 2016 ), we also examined the expression of stemness-related genes in the scramble and Bcl11b-KD cultures. As shown in Figure 2 , the expression of Sox2 – but not of Bmi1 – was reduced in Bcl11b-KD GPCs compared to that detected in the scramble culture.…”
Section: Resultsmentioning
confidence: 99%
“…Bcl11b has been reported to act as a transcriptional repressor to silence the expression of p21 ( Cherrier et al, 2009 ). Our previous study using human and rat glioma cells also showed that p21 expression was upregulated after the downregulation of Bcl11b expression in glioma cell lines, suggesting that Bcl11b is an important regulator for glioma cell expansion through the repression of p21 action ( Liao et al, 2016 ). The results from the present study showing that the proliferation of GPCs in GM was suppressed after Bcl11b-KD along with the upregulation of p21, also indicate that Bcl11b is involved in the maintenance of GPC stemness via the repression of p21 expression.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study revealed BCL11B as a key regulator of T-cell differentiation and maturation 30 . Attenuation of BCL11B activity also greatly enhanced β-catenin signaling, indicating a repressive effect of BCL11B in the carcinogenesis of colorectal cancers 22,31. However, it was also reported that enriched BCL11B expression in highly tumorigenic glioma cells promoted cancer cell growth by regulating the expression of stemness-associated genes (SOX2 and BMI1) 32 . Furthermore, high BCL11B expression was necessary for mammary epithelial cells to maintain quiescence 33 .…”
Section: Discussionmentioning
confidence: 99%